2014
DOI: 10.7785/tcrt.2012.500388
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Characteristics of a PIN Diode for Radiotherapy Application

Abstract: The PIN diode developed by Bhabha Atomic Research Centre (BARC) was modified for its use as a dosimeter in radiation therapy. For this purpose the diode was mounted on a printed circuit board (PCB) and provided with necessary connections so that its response against irradiation can be recorded by a standard radiotherapy electrometer. The dosimetric characteristics of the diode were studied in Co-60 gamma rays as well as high energy X-rays. The measured sensitivity of this PIN diode is 4 nC/cGy which is about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…9 b, which is evaluated in Table 3 , accordingly. It can be found that the sensitivity of the B 60 sample is more than eight times greater than the PIN diode dosimeter at the therapy level which was studied by Kumar et al 51 . Also, the sensitivity of the B 60 nanocomposite dosimeter in this research is significantly higher than the conventional dosimeters in radiotherapy, whose sensitive volume is often filled with free-air.…”
Section: Resultsmentioning
confidence: 90%
“…9 b, which is evaluated in Table 3 , accordingly. It can be found that the sensitivity of the B 60 sample is more than eight times greater than the PIN diode dosimeter at the therapy level which was studied by Kumar et al 51 . Also, the sensitivity of the B 60 nanocomposite dosimeter in this research is significantly higher than the conventional dosimeters in radiotherapy, whose sensitive volume is often filled with free-air.…”
Section: Resultsmentioning
confidence: 90%
“…To evaluate the dose-rate dependence, doses of 50, 100, 200, and 400 MU were irradiated for the dose-rate settings of 100, 200, and 400 MU/min. The measured signal was normalized based on a dose rate of 200 MU, and the RSD (n = 3) for the value measured at 100 MU was calculated following the method reported in the diode study, and evaluated based on the reported diode error of 1.1% [ 18 , 19 ]. At this time, the results of the diode were as in [ 18 ], which was conducted under similar evaluation conditions to this study.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A number of diode dosimeters are commercially available from vendors such as Veridose (Cardinal Health Management Services, USA), Isorad (Sun Nuclear, USA), T60010 (PTW, Germany), and EDP (Scanditronix Wellhofer, Sweden. [ 80 ] Another device called as DIGIDOSE – digital pocket radiation dosimeter has been developed by BARC [ 81 ] for detection of X & Gamma radiation doses. It is based on a commercially available Silicon (Si) rectifier diode operating at a low reverse bias of about 4 V. [ 81 ] A TLD based ring type dosimeter by ISRN Dosimetry Lab [ 82 ] is also available as a commercial product which can be worn on the finger; in this case the film (lithium fluoride) produces luminescence based on its exposure to ionising radiation.…”
Section: Radiation Dosimetry Techniquesmentioning
confidence: 99%
“…A number of diode dosimeters are commercially available from vendors such as Veridose (Cardinal Health Management Services, USA), Isorad (Sun Nuclear, USA), T60010 (PTW, Germany), and EDP (Scanditronix Wellhofer, Sweden. [80] Another device called as DIGIDOSE -digital pocket radiation dosimeter The case houses both the MND and communications dongle and allows access to the USB Type-C port on communications dongle, b) WDD sensitivity in cps/nv as a function of source distance. The flux at the location of the detectors was determined by MCNP6 simulations by calculating the average flux in the phantom volume at each source location.…”
Section: Wearable Dosimeters In the Commercial Worldmentioning
confidence: 99%